Breastfeeding perceptions of first time mothers: A metaphor analysis - POTUR, DİLEK (My University, 2023)
Our purpose in the present study is to determine mothers’ perceptions of breastfeeding through metaphors. This is qual-itative, cross-sectional and descriptive study. The present study included 33 volunteer mothers who gave birth vaginally for the first time, received care in the postpartum service, and breastfed their babies at least 10 times. To reveal the meta-phors related to the concept of breastfeeding, each mother was asked to complete the sentence “Breastfeeding is like... because....” The perceptions of the mothers about breastfeed-ing were gathered under three main themes: positive, negative and neutral metaphors. The identified metaphors were divided into five categories: indescribable emotion, peace, healing, task and inflicting pain. The mothers produced more positive met-aphors about breastfeeding
Keywords: Hemşirelik; Kadın Hastalıkları ve Doğum Hemşireliği; Sağlık Bilimleri; Nursing; Gynecology and Obstetrics Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing